2022
DOI: 10.3389/fneur.2022.884002
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Tinnitus and Vertigo or Dizziness in a Cohort of Adult Long COVID Patients

Abstract: Tinnitus, vertigo and dizziness are symptoms commonly reported among Long and Post COVID patients, however the severity of these symptoms has not been assessed in large trials. Therefore, in this study a large cohort of Long COVID patients was surveyed about the presence and severity of tinnitus and vertigo or dizziness symptoms. The online survey was completed by a German cohort of 1,082 adult Long COVID patients after a mean period of 43.2 weeks ± 23.4 weeks after infection. Eighty percent were not fully vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
0
13
0
2
Order By: Relevance
“…3, 4). Four studies only reported data about neurological conditions other than the 13 selected (vertigo/dizziness, tinnitus, dysphonia, primary CNS lymphoma, and brain tumor) and therefore were excluded [22‒25]. The neurological conditions with reported prevalences higher than 20% during the acute phase of COVID-19 were anosmia/hyposmia (58.9; 95% CI: 47.4–70.0), fatigue (44.5; 95% CI: 32.9–56.5), headache (35.4; 95% CI: 27.8–43.4), encephalopathy (29.7; 95% CI: 16.2–45.1), cognitive impairment (24.8; 95% CI: 13.238.4) and cerebrovascular disease (21.0; 95% CI 7.6–38.2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, 4). Four studies only reported data about neurological conditions other than the 13 selected (vertigo/dizziness, tinnitus, dysphonia, primary CNS lymphoma, and brain tumor) and therefore were excluded [22‒25]. The neurological conditions with reported prevalences higher than 20% during the acute phase of COVID-19 were anosmia/hyposmia (58.9; 95% CI: 47.4–70.0), fatigue (44.5; 95% CI: 32.9–56.5), headache (35.4; 95% CI: 27.8–43.4), encephalopathy (29.7; 95% CI: 16.2–45.1), cognitive impairment (24.8; 95% CI: 13.238.4) and cerebrovascular disease (21.0; 95% CI 7.6–38.2).…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review and meta-analysis provides data about the prevalence of neurological manifestations from the literature published during the first two and a half years of the pandemic. The best evidence on the prevalence of neurological signs/symptoms/disorders in COVID-19 survivors came from large studies [24] or registries [10], meta-analyses of general long-COVID-19 manifestations [11,12], three neurology-specific metaanalyses with <15,000 COVID-19 cases [12][13][14], and meta-analyses of single neurological manifestations [26][27][28][29]. More than 1.5 million COVID-19 survivors from 46 different countries are represented in this review, and we have generated data about the trajectories of the neurological manifestations for up to 1 year after the acute phase of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological symptoms were prevalent, with 60% of long COVID reporting some degree of vertigo or dizziness. The need for collaborative treatment techniques in long COVID-19 clinics, including experts in otorhinolaryngology, is highlighted by the high prevalence of neurotological symptoms such as vertigo [18].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that individuals can experience auditory, vestibular, olfactory, and gustatory dysfunctions for an extended time following a COVID-19 infection ( 31 ). Additionally, numerous literature reviews have demonstrated that long-term COVID is frequently associated with tinnitus and olfactory and gustatory dysfunction ( 32 ). These findings are consistent with the results of our report.…”
Section: Discussionmentioning
confidence: 99%